Treatment outcomes of a stage 1 cognitive-behavioral trial to reduce alcohol use among human immunodeficiency virus-infected out-patients in western Kenya. - Papas, Rebecca K; Sidle, John E; Gakinya, Benson N; Baliddawa, Joyce B; Martino, Steve; Mwaniki, Michael M; Songole, Rogers; Omolo, Otieno E; Kamanda, Allan M; Ayuku, David O; Ojwang, Claris; Owino-Ong'or, Willis D; et al. (Addiction (Abingdon, England), 2011)
Dual epidemics of human immunodeficiency virus (HIV) and alcohol use disorders, and a dearth of professional resources for behavioral treatment in sub-Saharan Africa, suggest the need for development of culturally relevant and feasible interventions. The purpose of this study was to test the preliminary efficacy of a culturally adapted six-session gender-stratified group cognitive-behavioral therapy (CBT) intervention delivered by paraprofessionals to reduce alcohol use among HIV-infected out-patients in Eldoret, Kenya.
Keywords: Adult; Alcohol Drinking; Ambulatory Care; Cognitive Therapy; Counseling; Cultural Characteristics; Epidemics; Female; HIV Infections; Humans; Kenya; Male; Patient Compliance; Psychotherapy, Group; Regression Analysis; Treatment Outcome